Archer and Coach Communication at the 2020 Tokyo Olympics - Teguh Dwi Putranto (Universitas Majalengka, 2023)
In competition, communication between athletes and coaches is essential to the individual athlete's success in achieving peak performance. Communication is important and cannot be abandoned during matches and practice. The evolution of sports, including archery, has made communication in sports a crucial component. In archery matches, communication is increasingly intense in individual events. The research examined the communication between archers and archery coaches in South Korea during the 2020 Tokyo Olympics. Because South Korean Archery is one of the best Archery teams in the world. In addition, the South Korean Archery dominated almost all numbers that were contested and brought South Korea to the top of the standings. Semiotics (Peirce) was used to analyse archery match finals of individual numbers in which South Korean archer participated. The results of this research revealed that communication between the archer and their coach was dominated by non-verbal communication in individual numbers symbolised by the high five.